PENERAPAN SANKSI PIDANA TERHADAP PENAMBANG BATU BARA ILEGAL MENURUT PERATURAN DAERAH NOMOR 12 TAHUN 2013 TENTANG PERTAMBANGAN MINERAL DAN BATU BARA DI WILAYAH KOTA SAMARINDA - Muhammad Rizal (Journal of Law ( Jurnal Ilmu Hukum ), 2022)
ABSTRACT Illegal mining is a mining business carried out by individuals, groups of people, or foundation companies with legal entities which in their operations do not have permits and government agencies in accordance with applicable laws and regulations. One area that has the potential for rock mining is Samarinda City, with the abundance of rock mining potential in Samarinda City attracting investors to invest in Samarinda City. However, there are also parties who carry out rock mining without fulfilling the procedures set by the government with various factors, such mining is called illegal mining. This writing uses the legal basis of Regional Regulation No. 12 of 2013 concerning minerals and coal and this research uses a normative method. Data sources consist of secondary data consisting of books, journals, laws and regulations related to research problems, data collection techniques are carried out by conducting document studies which are information data, scientific writings. This study uses the problem formulation: How is the application of illegal mining sanctions to the Samarinda City Regional Regulation Number 12 of 2013 concerning mineral and coal mining within the Samarinda City area and what are the government's efforts in dealing with illegal mineral and coal mining within the Samarinda City area which resulted in this research. may be imposed on the perpetrators of illegal coal mining in accordance with Article 90 of Regional Regulation Number 12 of 2013 concerning Coal Mineral Mining in the City of Samarinda, namely those who violate the provisions of the mineral and coal mining management permit as regulated in this regional regulation shall be punished with imprisonment for a maximum of 10 (ten) year and a fine of Rp. 10,000,000,000, - (ten billion rupiah). The Regional Government of Samarinda City through law enforcement officials and related agencies needs to be more serious and firm in terms of law enforcement against all legal coal mining activities in Samarinda City, If illegal coal mining activities continue to be carried out without proper supervision and management, it will cause severe pollution and environmental damage, of course this will result in losses to the people of Samarinda City. Keywords: Illegal Mining, Criminal